A Bad Commute: Travel Time to Work Predicts Teacher Turnover and Other Workplace Outcomes - Francisco Arturo Santelli; Jason A. Grissom (SAGE Publishing, 2024)
Research suggests that longer commute times may increase employee turnover probabilities by increasing stress and reducing job attachment and embeddedness. Using administrative data from a midsized urban school district, we test whether teachers with longer commute times are more likely to transfer schools or exit the district. Both descriptively and in regression results employing multiple fixed effects, we find that teachers with longer commutes are more likely to transfer schools within the district. Regression results show that each 5-minute increase in one-way commute time predicts an increase in transfer probability of 0.8 to 1.0 percentage points over most of the commute time distribution. We also find evidence that teachers with the longest commutes (i.e., 40+ minutes each way) have higher district exit probabilities. Moreover, teachers with longer commute times are absent from work more frequently and receive lower observation ratings. We discuss potential implications for local human resources policy and practice.